2011
DOI: 10.1186/ar3531
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon pathway in adult and juvenile dermatomyositis

Abstract: Gene expression profiling and protein studies of the type I interferon pathway have revealed important insights into the disease process in adult and juvenile dermatomyositis. The most prominent and consistent feature has been a characteristic whole blood gene signature indicating upregulation of the type I interferon pathway. Upregulation of the type I interferon protein signature has added additional markers of disease activity and insight into the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 42 publications
7
94
1
2
Order By: Relevance
“…This type 1 IFN profile was found to reflect disease activity in both DM and PM patients, highlighting its potential as a possible biomarker [72,[84][85][86][87]. The serum levels of IFN-α were found to be significantly higher in DM, PM and IMNM patients compared to IBM.…”
Section: Blood/serummentioning
confidence: 84%
See 1 more Smart Citation
“…This type 1 IFN profile was found to reflect disease activity in both DM and PM patients, highlighting its potential as a possible biomarker [72,[84][85][86][87]. The serum levels of IFN-α were found to be significantly higher in DM, PM and IMNM patients compared to IBM.…”
Section: Blood/serummentioning
confidence: 84%
“…Such gene array studies have identified a prominent type I IFN genetic signature in DM muscle in comparison with other forms of myositis [72,78]. However, expression of IFN-α and IFN-β and their inducible genes is not exclusively specific to DM and also occurs in PM [1,78], and PM patients have shown responsiveness to anti-IFN-α therapy [73,79].…”
Section: Muscle Tissuementioning
confidence: 99%
“…Total RNA was isolated using the RNeasy minikit (Qiagen) per the manufacturer's instructions. 1 g of total cellular mRNA was reverse transcribed into cDNA using the Omniscript RT kit (Qiagen) and oligo(dT) [12][13][14][15][16][17][18] primers (Life Technologies). Realtime PCR was carried out using an ABI7500 sequence detection system (Applied Biosystems) using commercially available FAM-labeled probes and primers (Applied Biosystems) to determine mRNA expression of Ip10, Dapk1, Slfn2, and Gapdh.…”
Section: ϫ/ϫmentioning
confidence: 99%
“…Interferons (IFNs) are pleiotropic cytokines that possess antiviral, immunomodulatory, growth-inhibitory, and cytotoxic properties (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). IFNs were among the earliest biologic therapeutic agents used to treat viral infections, certain solid tumors, hematologic cancers, and some autoimmune disorders (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation